The impact of internal audit quality on fighting corruption in the Qatari public sector - El-Hussaein, Omer Mahgoub (Journal of Economic, Administrative and Legal Sciences, 2024)
This study aimed to investigate the role of internal audit quality in preventing corruption in the public sector in Qatar State, as reflected in the indicators of independence, efficiency, honesty, and supervision carried out by the proper administration and transparency. The measures of effective internal audit lead to the provision of quality which guarantee the detection and prevention of Corruption; because its measures verify the accuracy of financial data, optimization of resource prevention of corruption and embezzling money, and protection of assets and resources. The importance of audit stems from the measures used to reduce, and combat corruption, which has become a dangerous phenomenon that hinders Es growth, which may cause political turmoil, and divisions in the society, and result in the waste of resources and assets of the State. No doubt the international community is concerned about the phenomena of corruption, and for this reason, cooperative measures are set for anti-corruption practices. The researcher adopted the descriptive analytical approach, using a questionnaire directed to experts and professionals to collect data to verify the hypotheses of the study. The study sample consisted of (35) internal auditors (male-female) working in the public sector in Qatar. Analysis of the data revealed a number of results the importance of which is; the independence and integrity of the internal auditor, comes first in fighting corruption. In addition to that, the efficacy of the auditing process and achieving its goals have great effects on anti-corruption in the public sector. Furthermore, the establishment of anti-corruption organizations helps much in fighting corruption. Corruption has serious results on the economy, and the growth security of the community; to evade these dangers; the international community has to face it collectively. The study showed that the International Standards of internal audit do not lay any responsibility on the part of the internal auditor if its evidence of fraud is vague or ambiguous.